Subjective and objetive validity - Reyna, Rafael (Con-Textos Kantianos. International Journal of Philosophy, 2024)
This article explores the distinction between the universal validity of judgments of experience, as it appears in the Prolegomena, in relation to the concept of subjective universal validity in the Critique of Judgment. In doing so, it is expected to show some systematic aspects of Kant’s treatment of both notions. The hermeneutical basis of this approach is to be found in Wieland’s seminal work, Urteil und Gefühl. This paper also seeks to share the originality and depth of his proposal.